2016
DOI: 10.1007/s00418-016-1440-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative imaging of Rac1 activity in Dictyostelium cells with a fluorescently labelled GTPase-binding domain from DPAKa kinase

Abstract: Small Rho GTPases are major regulators of the actin cytoskeleton dynamics in eukaryotic cells. Sophisticated tools used to investigate their activity in living cells include probes based on fluorescence resonance energy transfer (FRET), bimolecular fluorescence complementation, and photoactivation. However, such methods are of limited use in quickly migrating cells due to a short time available for image acquisition leading to a low signal-to-noise ratio. Attempts to remedy this effect by increasing the intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 76 publications
(80 reference statements)
2
12
0
Order By: Relevance
“…In D. discoideum , GxcU-GFP was recruited to several distinct stages of the endocytic pathway (Figure 4), both at what would be considered very early (at the base of the macropinocytic crown) and at the site of reforming CVs, several seconds after the timepoint when the other F&H interactor, OIBP-GFP, appears (e.g., Figure 5A). While the target of the GxcU GEF activity is not known, the localization of GxcU to macropinosomes is highly reminiscent of the localization of active Rac1 (Marinovic et al , 2016; Rivero and Xiong, 2016). Interestingly, overexpression of GxcU-GFP phenocopied Dd5P4 loss in terms of fluid-phase dye uptake and processing and enhanced the Dd5P4 - mutant phenotype (Figure 7), suggesting that Dd5P4 may be a repressor of GxcU function.…”
Section: Discussionmentioning
confidence: 99%
“…In D. discoideum , GxcU-GFP was recruited to several distinct stages of the endocytic pathway (Figure 4), both at what would be considered very early (at the base of the macropinocytic crown) and at the site of reforming CVs, several seconds after the timepoint when the other F&H interactor, OIBP-GFP, appears (e.g., Figure 5A). While the target of the GxcU GEF activity is not known, the localization of GxcU to macropinosomes is highly reminiscent of the localization of active Rac1 (Marinovic et al , 2016; Rivero and Xiong, 2016). Interestingly, overexpression of GxcU-GFP phenocopied Dd5P4 loss in terms of fluid-phase dye uptake and processing and enhanced the Dd5P4 - mutant phenotype (Figure 7), suggesting that Dd5P4 may be a repressor of GxcU function.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 5A ). While the target of the GxcU GEF activity is not known, the localization of GxcU to macropinosomes is highly reminiscent of the localization of active Rac1 63,64 . Interestingly, overexpression of GxcU-GFP phenocopied Dd5P4 loss in terms of fluid-phase dye uptake and processing and enhanced the Dd5P4 - mutant phenotype ( Figure 7 ), suggesting that Dd5P4 may be a repressor of GxcU function.…”
Section: Discussionmentioning
confidence: 99%
“…The postulated role of Rac in the activation of Dicytostelium SCAR is further corroborated by the colocalization of active Rac and SCAR [ 112 , 128 ]. Moreover, the cellular distribution of a probe specific for Dicytostelium Rac1 GTPases [ 131 ] shows that SCAR localizes to the structures occupied by active Rac1: the leading edges of pseudopodia [ 112 ], macropinosomes, and phagosomes [ 132 ] and the protruding poles of incipient daughter cells during cell division [ 133 ]. Of note, more detailed analysis of macropinocytic and phagocytic cups revealed that Rac is located at the cup centre, while SCAR localizes to the rim of nascent cups [ 132 ].…”
Section: Comparative Analysis Of the Rho Signalling In Dictyostelium And Mammalian Cellsmentioning
confidence: 99%
“…Although no clear functional significance of the PAKa interaction with Rac GTPases has been deciphered yet, its GBD was successfully used to track and quantify the spatio-temporal activity of Rac1 in Dictyostelium cells [ 131 ]. Y2H, pull-down, and fluorescence resonance energy transfer (FRET) assays showed that PAKa GBD specifically interacts with the active Rac1A, and the fluorescently labelled probe localizes to the leading edge of migrating cells and to endocytic cups [ 131 ].…”
Section: Comparative Analysis Of the Rho Signalling In Dictyostelium And Mammalian Cellsmentioning
confidence: 99%